From agricultural waste to antioxidant treasure: valorization of Astragalus stems through high-pressure steam explosion-derived polysaccharides with dual ROS-scavenging and embryoprotective effects - Yuning An; Yuan Wang; Mu Qier; Wenwen Wang; Yanbin Wang; Yuquan Wang; Xiaoping An (Chemical and Biological Technologies in Agriculture)
Abstract Astragalus, a traditional Chinese medicinal herb, has been widely utilized. However, its stems (AS) are often discarded as agricultural waste. High-pressure steam explosion (HPSE) is an effective technique for disrupting plant cell walls and releasing bioactive substances. In this study, a novel antioxidant crude polysaccharide (HPSEASCP) was developed from AS through HPSE pretreatment combined with water extraction, ethanol precipitation, and protein removal. The bioactive components, structural composition, and antioxidant properties of HPSEASCP were systematically evaluated both in vitro and in vivo. Results demonstrated that HPSE pretreatment significantly enhanced the antioxidant capacity of ASCP by reducing molecular weight, increasing uronic acid levels, and promoting the release of polysaccharide, bound polyphenols and flavonoids, thereby enriching its bioactive components. Importantly, these modifications preserved the core β-polysaccharide structure and functional groups. HPSEASCP exhibited significantly higher DPPH radical scavenging activity, hydroxyl radical scavenging activity, and reducing power compared to ASCP. In vivo studies leveraging a zebrafish model revealed that 25 μg/mL HPSEASCP effectively improved embryo survival and hatching rates while alleviating AAPH-induced oxidative stress. Concretely, HPSEASCP reduced reactive oxygen species (ROS) generation, suppressed lipid peroxidation levels, and decreased cell death rates in embryos under oxidative stress conditions, thereby promoting healthy larval development. These findings highlight the remarkable antioxidant potential of HPSEASCP as a candidate for functional food or pharmaceutical applications while providing new insights into the valorization of AS agricultural waste. Graphical Abstract